Economic Evaluation of Soil and Water Conservation Practices and Forage Mixtures Cropping Under Different Agroecosystems in Northern and Central West Tunisia - Souissi, Asma; Dhehibi, Boubaker; Frija, Aymen; M. Oumer, Ali; Idoudi, Zied; M'hamed, Hatem Cheikh; Ben Youssef, Salah; Bahri, Haithem; Le, Quang Bao; Shiri, Zahra; Wafa, Ameur; Ouerghemmi, Hassen; et al. (International Center for Agricultural Research in the Dry Areas, 2023)
Soil erosion and land degradation are critical challenges in Northern and Central West Tunisia. This report assesses the profitability of different forage mixtures used as a key rotation practice to mitigate these challenges. Various soil and water conservation (SWC) practices were put in place using a sample of 33 small farmers in the framework of the SWC@Scale-ProSol project. Cost-benefit and a partial budget analysis were conducted to assess the profitability of the implemented agricultural practices on the selected demonstration plots. Technical and economic surveys were also carried out and forage samples were collected to support the study. Results show that the four tested forage mixtures were profitable in both agroecosystems of the study (Siliana and Kairouan), particularly under the rainfed agriculture production system. The mixture “Vetch-Oat-Triticale” (VOT) has the best net return and benefit-cost ratio. SWC practices, such as the zero and/or minimum tillage and the mechanical sowing, also increase the benefit-cost ratio (BCR). The intercropping system (forage mixtures between lines of olive trees) reached a net return and a BCR remarkably close to the open field cropping system. Using forage mixtures and applying SWC practices significantly contributes to curbing the growing erosion problems in the studied areas, as well as enhancing farmer’s profitability, and can thus widely be considered an option for both profitability and sustainability.